TANGGUNG JAWAB DIREKSI ANTAM TERHADAP PERJANJIAN DIAM-DIAM DALAM TRANSAKSI EMAS ANTAM: Liability Of Antam Directors For Silent Agreements In Antam Gold Transactions - Muhammad Farrell; Sri Bakti Yunari (Faculty of Law, Universitas Trisakti, 2024)
The responsibilities of the Board of Directors in a Limited Liability Company are regulated under Article 92 of Law No. 40 of 2007, establishing a fiduciary relationship for the Directors. The secret gold sale agreement at BELM Surabaya Branch 01 by non-employees led to the Directors of PT. Antam Persero Tbk being held accountable. This article addresses: What are PT. Antam's Directors' responsibilities regarding the secret gold sale agreement? and How does Decision No.1666/K/Pdt/2022 align with holding PT. Antam accountable? This study uses a normative descriptive legal method with secondary data analyzed qualitatively for deductive conclusions. The analysis shows that the Directors cannot be held accountable because they fulfilled their fiduciary duty by implementing the SOP on commodity pricing. The judge's decision was based on Article 1367 of the Civil Code, not Article 97 (5) of the Company Law, as the loss was not due to employee negligence. In conclusion, PT. Antam's directors are not responsible for the secret gold sale agreement since they complied with SOP 700 01. Additionally, the judge's decision can be criticized because the secret agreement by Eksi Anggraen and Budi Said does not meet subjective requirements, making it invalid for PT. Antam and revocable.